IMPLEMENTASI PENDEKATAN BACKENDLESS DALAM RAPID PROTOTYPING APLIKASI MANAJEMEN PENUGASAN KARYAWAN - Phan, Irwan Kurnia; Yuricha, Yuricha (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Web application development has reached the point where developing an application will need developers to consider a whole lot of aspects in development such as server infrastructures, server security, database, APIs, programming language, and operating systems. These aspects lead to complex activities that require developers to have a long learning and development curve. There are existing possible ways to design and develop an application without developers have to learn and do all of things that had mentioned above. One of existing solution is the backendless approach using provisioned services from third party. In this article, an employee assignment management web-based application is designed and developed as prototype with the ability to create, assign, view and browse list of assignments using backendless approach. Backendless approach also enable rapid prototyping which developers can shorten time-to-market and get feedback from users as fast as possible to deliver solution.